(untitled) (Global Journal of Human-Social Science, 2022)
The crime of premeditated murder is an act or crime that can kill the life of another person Losing the life of another person here is done by the perpetrator or some perpetrators which results in the deprivation of another person s life by the deliberate form of the perpetrator Such as crimes or criminal acts committed by Djumanan Tasrip and also Satuwi who attempted to commit premeditated murder by Tosan Victims where they tortured the victim by beating the victim and also protecting the victim The problem raised in this thesis is whether the offender s actions comply with Article 340 of the Criminal Code in conjunction with Article 55 paragraph 1 of the Criminal Code or Article 351 2 in conjunction with Article 170 paragraph 2 of the Criminal Code in conjunction with Article 55 of the Criminal Code In the study of Decision Number 265 K Pid 2017 and are the sanctions imposed by the Judge in accordance with the theory of the purpose of punishment In the Decision Study Number 265 K Pid 2017 The research method used in this problem is the normative juridical research method the nature of the descriptive analysis research the data collection by using literature study while the conclusion is drawn using deductive logic Based on the analysis of the actions carried out by Djumanan Tasrip and Besri they have fulfilled Article 340 in conjunction with Article 55 of the Criminal Code which consists of whoever deliberately planned in advance and killed another person s life However the Judge decided that the Defendants were subject to Article 170 2 of the Second Criminal Code with 9 years imprisonment each Regarding the problem regarding the sanctions imposed by the Judge in the theory of the purpose of punishment in this case is a relative theory namely a theory that aims to lead to the welfare of the community without any revenge